Numerical Simulation of a Physiological Mathematical Model of Energy Consumption in a Sarcomere: Simulation of a sarcomere - Flores Rodríguez, Kathia Gabriela; Pérez Garza, David Edel; Quiroz, Griselda (Revista Mexicana de Ingenieria Biomedica, 2021)
Systems Biology of (SB) offers a platform for analyzing biological processes from the perspective of systems theory based on qualitative knowledge of the biological sciences to generate quantitative knowledge. The area of SB devoted to human health is called Systems Medicine. It studies physiological processes, pathological conditions, and recommended treatments with the goal of providing quantitative elements for optimizing medical treatments. Two analytical tools of SB are mathematical modelling and numerical simulation. The first offers a quantitative abstraction of processes; the second involves implementing computer-based models to reproduce and visualize the variables for purposes of prediction. This article presents a case of the application of mathematical modelling and numerical simulation to the physiological process of energy consumption in the sarcomere of skeletal muscle. It proposes a model that includes activation of the contractile cycle based on the action potential that reaches the neuromuscular union, calcium release into the sarcoplasm, the mechanical response, and quantification of the energy that the sarcomere requires to perform mechanical work.